2019
DOI: 10.1021/acsami.9b00392
|View full text |Cite
|
Sign up to set email alerts
|

All-Solid-State Synaptic Transistors with High-Temperature Stability Using Proton Pump Gating of Strongly Correlated Materials

Abstract: Designing energy-efficient artificial synapses with adaptive and programmable electronic signals is essential to effectively mimic synaptic functions for brain-inspired computing systems. Here, we report all-solid-state three-terminal artificial synapses that exploit proton-doped metal–insulator transition in a correlated oxide NdNiO3 (NNO) channel by proton (H+) injection/extraction in response to gate voltage. Gate voltage reversibly controls the H+ concentration in the NNO channel with facile H+ transport f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 41 publications
0
45
0
Order By: Relevance
“…Given the feature of flexible operation for tuning the channel conductance, IGTs are favorable for artificial synaptic devices and thereby being used for neuromorphic computing. [137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153] Figure 6. a) Alcohol detection by simply breathing on the OECT-based sensors.…”
Section: Neuromorphic Computingmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the feature of flexible operation for tuning the channel conductance, IGTs are favorable for artificial synaptic devices and thereby being used for neuromorphic computing. [137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153] Figure 6. a) Alcohol detection by simply breathing on the OECT-based sensors.…”
Section: Neuromorphic Computingmentioning
confidence: 99%
“…[ 109–136 ] Given the feature of flexible operation for tuning the channel conductance, IGTs are favorable for artificial synaptic devices and thereby being used for neuromorphic computing. [ 137–153 ]…”
Section: Neuromorphic Computingmentioning
confidence: 99%
“…As δ increases in VO 2− δ channels, the H + is incorporated into a much “deeper” region from the electrolyte/VO 2− δ interfaces (Figure 2e); these results clearly demonstrate that the deep penetration of H + during application of V G is facilitated by preformed oxygen vacancies in VO 2− δ layers; H + are inserted more deeply into the VO 2− δ lattice than into the VO 2 lattice, so the VO 2− δ lattice retains more residual (or trapped) H + than the VO 2 lattice does. [ 6,9,15 ]…”
Section: Figurementioning
confidence: 99%
“…[ 2 ] Unlike the devices using transport of oxygen ion (via oxygen vacancies), [ 2,3 ] H + as an extrinsic defect can be externally inserted into a target VO 2 channels to alter conductivity and induce phase transition between insulating and metallic phase without disrupting the crystal lattice framework [ 6,10,13 ] ; this smallest and lightest ions can increase the switching speed at low voltage in insertion transistors. [ 4,6,10,15 ]…”
Section: Figurementioning
confidence: 99%
“…Here, we show that tree-like structures can be experimentally realized at room temperature in strongly correlated rare-earth perovskite nickelates (ReNiO 3 , where Re is a rare-earth ion), a class of quantum materials whose electrical properties are largely dominated by the strong interactions among electrons in them [28][29][30] . For example, in NdNiO 3 and SmNiO 3 , prior studies have shown that hydrogen doping results in several orders of magnitude change in electrical resistance via modifying electron occupancy of the Ni orbitals 31,32 . When hydrogen molecules are split by a catalytic electrode into hydrogen atoms and doped into the rare-earth perovskite nickelate lattice, the electron from the hydrogen atom is injected to the Ni e g orbital, while the proton resides in interstitial sites.…”
mentioning
confidence: 99%